PENGARUH PEMBERIAN L-ARGININE TERHADAP JUMLAH SEL SERTOLI DAN SEL LEYDIG MENCIT (Mus musculus) SETELAH DIPAPAR SUHU PANAS - KHADIJAH KHAIRUL BARIYAH, 061311133052 (2019)
The purpose of this study was to know the effect of L-arginine on the number of Sertoli cells and Leydig cells in mice (Mus musculus) after heat temperature exposed. The subjects of this study were 30 male mice, 8 weeks old. This research conducted by using Randomized Block Design (RAK) with experimental group 2x3 factorial design with 5 replications. Group I: without high-temperature exposure (P0) and a high-temperature exposure (P1). Group II: the dose of L-arginine 0mg (A0), 1,3mg (A1), dan 2,6mg (A2). The treatment consists of, control group (-) P0A0 = treatment with aquabidest without high-temperature exposure. P0A1 = treatment with a dose of 1,3mg L-arginine without high-temperature exposure. P0A2 = treatment with a dose 2,6mg of L-arginine without high-temperature exposure. Control group (+) P1A0 = treatment with aquabidest with high-temperature exposure. P1A1 = treatment with a dose of 1,3mg L-arginine with high-temperature exposure. P1A2 = treatment with a dose 2,6mg L-arginine with high-temperature exposure. Sertoli cells and Leydig cells were calculated and analyzed using Two Way ANOVA followed by Duncan Test. The results of this study were: (1) The treatment of heat temperature can reduce the number of Sertoli cells and Leydig cells in mice (p<0,05); (2) The treatment with L-arginine orally to mice can increase the number of Sertoli cells with a dose 1,3 mg and Leydig cells with a dose 2,6 mg (p<0,05); (3) There is no interaction between the heating temperature and the doses of L-arginine to the number of Sertoli cells and Leydig cells in mice (p>0,05).